P(AN-co-MMA) nanofiber membrane decorated with greenly synthesized nanoparticles for heavy metal removal: a competitive study - Abeer Syed; Enshirah Da’na; Amel Taha; Mohamed R El-Aassar; Adnan M Aldughaish (Materials Research Express)
Heavy metal contamination is a serious threat to water resources as it has been associated with carcinogenicity, mutagenicity, and toxicity. With the presence of heavy metals in water bodies reported from all over the globe, there is an urgent need for innovative water treatment strategies. The main goal of this study is to enhance the adsorption affinity of poly(acrylonitrile-co-methyl methacrylate) (P(AN-co-MMA)) nanofiber membrane for heavy metals by decorating the nanofiber membrane with greenly synthesized CoFe _2 O _4 nanoparticles. Field emission scanning electron microscopy (FESEM) and transmission electron microscope (TEM) images confirmed the uniform dispersion of 30–40 nm CoFe _2 O _4 nanoparticles within the P(AN-co-MMA) nanofiber membrane, having an average fiber diameter of 269 nm. x-ray diffraction (XRD) analysis showed the formation of highly crystalline CoFe _2 O _4 nanoparticles without impurities. The CoFe _2 O _4 nanoparticles exhibited type-IV isotherm, indicating the formation of mesoporous/macroporous materials with a specific surface area of 36.8 m ^2 g ^−1 . Thermal gravimetric analysis (TGA) demonstrated that both P(AN-co-MMA) and P(AN-co-MMA)CoFe _2 O _4 begin to decompose at around 340 °C. The competitive adsorption behavior of the CoFe _2 O _4 , P(AN-co-MMA), and P(AN-co-MMA)CoFe _2 O _4 was studied to determine their selectivity towards Pb ^2+ , Hg ^2+ , and Cd ^2+ . The results showed a superior affinity of CoFe _2 O _4 nanoparticles for Cd ^2+ , with 100% removal within a concentration range of 20–80 ppm, compared to 50% removal using P(AN-co-MMA)CoFe _2 O _4 , and zero removal with P(AN-co-MMA). For Hg ^+ , the efficiency of removal by the CoFe _2 O _4 was the highest followed by P(AN-co-MMA), and then P(AN-co-MMA) CoFe _2 O _4 . Pb ^2+ showed exclusive affinity for the CoFe _2 O _4 nanoparticles only. The presented eco-friendly nanocomposite presents a promising, efficient, and selective adsorbent for heavy metal removal from wastewater to address water pollution.